Possibility of the total reflection x-ray fluorescence spectrometer for the determination of lead in biological samples - Ts, Javzandolgor; Ts, Amartaivan; Ch, Buyantogtokh; B, Bilguun; B, Lkham; Ya, Ganbold (Mongolian Journal of Agricultural Sciences, 2019)
Mongolia has been exposed to extreme draught and dry summer for its historical development due to geographical location, climatic condition, surface characteristics and being subject to vulnerable and dry region in terms of ecological system. Besides it, rapid increase in the minerals production has been causing heavy metal pollution in soil, water and plants. Soil pollution is main parameter of environmental pollution and air and water pollution directly depend on it. Main influencing factor of endemic diseases of livestock is chemical ingredient of soil, water and plant. Due to negligent use and disposal of lead containing sources including acid and alkali batteries with lead conductor, vehicle accumulators in last years, environment has been polluted greatly and it becomes the cause of animal poisoning. Heavy metals are dangerous because of their persistence and toxicity. Soil behaves as a sink of heavy metals by aerial deposition of particles emitted by human activities. The aims of this work were to identify the levels of lead in accumulator processing plant and city areas and animals. We have determined lead level in biological samples /livestock blood/ using total reflection X-ray fluorescence spectrometer and compared the results found by the Lead Care II. Бүрэн ойлтын рентгенфлоуресценцийн спектрометр ашиглан биологийн дээжинд хартугалга тодорхойлох боломж Хураангуй: Монгол орон газар зүйн байршил, уур амьсгалын нөхцөл, газар нутгийн гадаргын хэв шинж, экологийн тогтолцооны хувьд нэн эмзэг, хуурай бүс нутагт хамрагддагийн улмаас түүхэн хөгжлийнхөө турш ган, зуданд нэрвэгдсээр ирсэн байна. Үүний зэрэгцээ манай оронд ашигт малтмалын олборлолт эрс нэмэгдсэнээр хөрс, ус, ургамал хүнд металлаар ихээр бохирдох боллоо. Хөрсний бохирдол нь байгаль, орчны төлөв байдлын гол үзүүлэлт бөгөөд агаар, усны бохирдол үүнээс шууд хамаарна [1]. Мал, амьтны нутгийн орогнол (эндемик) өвчинд гол нөлөөлөх зүйл бол хөрс, ус, ургамлын химийн найрлага юм. Хар тугалган дамжуулагч бүхий хүчлийн болон шүлтийн батарей, автомашины аккуммулятор зэрэг хар тугалга агуулсан эх үүсвэрүүдийг эмх замбараагүй хаясны улмаас байгаль орчин хар тугалгаар ихээр бохирдож мал, амьтны хордох шалтгаан болж байна. Хар тугалгыг мэдрэлийн хор гэж нэрлэдэг бөгөөд өсөлт, тархины хөгжлийг саатуулах аюултай. Иймд бид бүрэн ойлтын рентген флуоресценцийн аргыг ашиглан биологийн дээжинд (малын цусанд) хар тугалганы хэмжээг тодорхойлон, үр дүнг LeadCare II багажийн хэмжилтийн дүнтэй харьцуулав. Бидний хийсэн хэмжилтийн дүнгээс харахад 2 багажийн тоон үзүүлэлт хамаарлын шугаманд ойролцоо гарч байна. Түлхүүр үг: Хүнд метал, үхэр, цус, дээж